Air exchange rates and advection–diffusion of CO2 and aerosols in a route bus for evaluation of infection risk. (20th March 2022) - Shinohara, Naohide; Tatsu, Koichi; Kagi, Naoki; Kim, Hoon; Sakaguchi, Jun; Ogura, Isamu; Murashima, Yoshiko; Sakurai, Hiromu; Naito, Wataru
Abstract: As COVID‐19 continues to spread, infection risk on public transport is concerning. Air exchange rates (ACH) and advection–diffusion of CO2 and particles were determined in a route bus to evaluate the infection risk. ACH increased with bus speed whether windows were open or closed, and ACH were greater when more windows were open. With two open windows, ACH was greater when a front and rear window were open than when two rear windows were open. With both front and rear ventilation fans set to exhaust, ACH was more than double that when both were set to supply. With air conditioning (AC) off, CO2 and particles spread proportionally at the same rate from a source, whereas with the AC on, the spread rate of particles was about half that of CO2, because particles might be trapped by a prefilter on the AC unit. Infection risk can be reduced by equipping AC unit with an appropriate filter. Calculations with a modified Wells–Riley equation showed that average infection risk was reduced by 92% in the moving bus with windows open comparing to with windows closed. When the bus was moving with windows closed, exhaust fan operation reduced the average risk by 35%.